2001
DOI: 10.1364/oe.9.000417
|View full text |Cite
|
Sign up to set email alerts
|

Study of local cerebral hemodynamics by frequency-domain near-infrared spectroscopy and correlation with simultaneously acquired functional magnetic resonance imaging

Abstract: Abstract:The aim of our study was to explore the possibility of detecting hemodynamic changes in the brain using the phase of the intensity modulated optical signal. To obtain optical signals with the highest possible signal-to-noise ratio, we performed a series of simultaneous NIRS-fMRI measurements, with subsequent correlation of the time courses of both measurements. The cognitive paradigm used arithmetic calculations, with optical signals acquired with sensors placed on the forehead. Measurements were done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 19 publications
2
49
0
Order By: Relevance
“…This allows comparisons of the spatial and temporal characteristics of the fMRI signals with optically-derived hemodynamic changes to clarify the contributions of different physiological parameters to the fMRI signals. Several studies of functional activations have been performed in the human motor cortex by simultaneous fMRI and NIRS (Toronov et al, , 2001b(Toronov et al, , 2003a. In particular it was found that, in the human motor cortex, the temporal dependence of the deoxyhemoglobin concentration was the factor most closely related to the BOLD fMRI signal.…”
Section: Introductionmentioning
confidence: 99%
“…This allows comparisons of the spatial and temporal characteristics of the fMRI signals with optically-derived hemodynamic changes to clarify the contributions of different physiological parameters to the fMRI signals. Several studies of functional activations have been performed in the human motor cortex by simultaneous fMRI and NIRS (Toronov et al, , 2001b(Toronov et al, , 2003a. In particular it was found that, in the human motor cortex, the temporal dependence of the deoxyhemoglobin concentration was the factor most closely related to the BOLD fMRI signal.…”
Section: Introductionmentioning
confidence: 99%
“…(Franceschini et al, 2000;Kennan et al, 2002;Colier et al, 2001;Obrig et al, 2002;Sato et al, 1999;Hoshi et al, 2000) The compatibility of optical imaging with other neuroimaging methods has received wide interest. Optical measurements have been successfully combined with fMRI (Kleinschmidt et al, 1996;Toronov et al, 2001), MEG (Mackert et al, 2002), EEG (Kennan et al, 2002;Israel et al, 2002) and TMS (Oliviero et al, 1999;Iwata et al, 2000;Nissilä et al, 2002b). Figure 13.…”
Section: 31d Practical Applicationsmentioning
confidence: 99%
“…Calculations of Hb and HbO 2 concentration changes have been performed by the well established ''modified Beer-Lambert law'' [12,27,31,35]. There has been some controversy in the literature on whether neuronal activation should be monitored with Hb, HbO 2 , Oxygenation (HbO 2 -Hb), or total Hb (THb = HbO 2 + Hb) [1,7,10,11,15,24,27,28,[32][33][34]36]. While most of these studies stress that HbO 2 reflects neuronal activation more reliably and consistently, some others have shown that this effect is only global.…”
Section: Measurementsmentioning
confidence: 99%
“…We have also observed similar changes during the course of the whole experiment. Such variability or even the absence of the expected cognitive response may be attributed to the differences in the cerebrovascular physiology, attention level, and habituation of the subject [10,33,34].…”
Section: Temporal Iid Conditionsmentioning
confidence: 99%
See 1 more Smart Citation